2020
DOI: 10.1007/s00280-020-04119-8
|View full text |Cite
|
Sign up to set email alerts
|

Asian race and origin have no clinically meaningful effects on polatuzumab vedotin pharmacokinetics in patients with relapsed/refractory B-cell non-Hodgkin lymphoma

Abstract: Purpose The CD79b-targeted antibody–drug conjugate polatuzumab vedotin (pola), alone and with chemoimmunotherapy, has clinical efficacy and a tolerable safety profile in B-cell non-Hodgkin lymphoma (B-NHL). We assessed (a) whether exposure from global studies of pola is comparable to Asian patients, and (b) if the recommended pola dose is appropriate in Asian patients based on exposure. Methods The pharmacokinetics (PK) of pola in As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The PK profile of these analytes was generally consistent with that seen for pola monotherapy in the previous Japanese phase 1 study, 17 and also consistent with the pharmacokinetics for non-Asian patients in an ethnic sensitivity analysis. 25 Based on these cross-study comparisons, bendamustine and rituximab do not appear to have a clinically significant impact on the pharmacokinetics of pola, and there were no clinically meaningful differences in pola pharmacokinetics based on Japanese ethnicity. The number of patients with available samples for PK analysis.…”
Section: Discussionmentioning
confidence: 84%
“…The PK profile of these analytes was generally consistent with that seen for pola monotherapy in the previous Japanese phase 1 study, 17 and also consistent with the pharmacokinetics for non-Asian patients in an ethnic sensitivity analysis. 25 Based on these cross-study comparisons, bendamustine and rituximab do not appear to have a clinically significant impact on the pharmacokinetics of pola, and there were no clinically meaningful differences in pola pharmacokinetics based on Japanese ethnicity. The number of patients with available samples for PK analysis.…”
Section: Discussionmentioning
confidence: 84%
“…To search for Pola‐refractory cells, we tested sensitivity to Pola and calculated the IC 50 value in a panel of 11 DLBCL cells, comprising eight germinal centre B‐cell‐like (GCB)‐DLBCL (DB, STR‐428, SU‐DHL‐5, SU‐DHL‐10, SU‐DHL‐4, NU‐DUL‐1, SU‐DHL‐8 and HT) and three activated B‐cell‐like (ABC)‐DLBCL (U‐2932, SU‐DHL‐2 and RC‐K8) (Figure 1A; Figure S1A). We used an IC 50 = 1 μg/ml as the cut‐off value, based on the clinical trough drug concentration levels in the GO29365 study, 14 and identified four cells showing refractoriness to Pola.…”
Section: Resultsmentioning
confidence: 99%
“…The current study contributes additional information to the ethnic sensitivity landscape in a number of ways. It includes data from a broader Asian patient population than in previous studies; Shi et al 1 . used data from Japanese and South Korean patients, whereas here, data from Chinese, Japanese, South Korean, and Taiwanese patients were used.…”
Section: Discussionmentioning
confidence: 99%
“…Drug efficacy and safety can potentially vary between patients of different ethnicities due to factors including bodyweight, genetic polymorphisms in key metabolic enzymes, and regional standard‐of‐care practices 1,9 . For example, between Asian and non‐Asian patients, such differences can necessitate dose adjustments across patient subpopulations 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation